2018
DOI: 10.1186/s11671-018-2691-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Substrate to the LSP Coupling Wavelength and Strength

Abstract: Three kinds of typical structures, hemi-/spherical nanoparticles/nanoparticle dimers on the substrate and spherical nanoparticles/nanoparticle dimers half-buried into the substrate, are used for FDTD simulation to theoretically discuss the influence of the substrate to the localized surface plasmon (LSP) coupling when the metal nanoparticles/nanoparticle dimers are locating near a substrate. Simulated results show that the dependencies between the LSP coupling wavelength and the refractive index of the substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…This effect is stronger for greater contact between the nanoparticle and the substrate. 55,56 Although the effect of the substrate can be an important aspect to consider, its inclusion in the model entails greater consumption…”
Section: Problem Specification and Numerical Methodologymentioning
confidence: 99%
“…This effect is stronger for greater contact between the nanoparticle and the substrate. 55,56 Although the effect of the substrate can be an important aspect to consider, its inclusion in the model entails greater consumption…”
Section: Problem Specification and Numerical Methodologymentioning
confidence: 99%
“…We assume that the refractive index of the substrate is the same as that of the surrounding medium, water. Therefore, the reflected light will not be induced at the interface between the medium and the substrate; the optical field is not disturbed by the existence of the substrate [ 37 ]. On the other hand, the existence of the substrate serves as a confinement to support NPs moving on the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…CEM relies on the charge transfer between chemisorbed species and the metal surface [8] . EM provides the leading contribution (typically by a factor of 10 8 ) for the SERS enhancement, which generally originates from the magnification of the electric field by the excitation of LSPs of the underlying SERS active material [9] . One of the strategies is to improve the EM enhancement further by increasing the coupling with the LSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Theory predicts that the LSP coupling strongly depends on the separation distance between the nanoparticles (NPs), which have been confirmed experimentally. Thus, controlling the distance is a promising avenue to improve the SERS enhancement factor [9,10] . It has been observed that the EM enhancement can be drastically increased with the decrease of the separation distance between NPs [9,10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation